2009
DOI: 10.1099/vir.0.014977-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Alternanthera mosaic virus is affected by determinants in RNA-dependent RNA polymerase and by reduced efficacy of silencing suppression in a movement-competent TGB1

Abstract: Four biologically active cDNA clones were derived from the Alternanthera mosaic virus (AltMV; genus Potexvirus) isolate, AltMV-SP, which differ in symptoms in infected Nicotiana benthamiana plants. Two clones induced necrosis and plant death; a mixture of all four clones induced milder symptoms than AltMV-SP. Replication of all clones was enhanced by a minimum of fourfold at 15 6C. A mixture of clones 4-7 (severe) and 3-1 (mild) was indistinguishable from AltMV-SP, but the ratio of 4-7 to 3-1 differed at 25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 34 publications
6
89
0
1
Order By: Relevance
“…Ñõåìà ãåíîìà AltMV-MU è ñîçäàííûõ íà åãî îñíîâå âèðóñíûõ âåêòîðîâ: A -ãåíîì AltMV-MU; Á -AltMV-triple1;  -AltMV-triple2. ÒÁ 1, 2, 3 -ãåíû òðåõ òðàíñïîðòíûõ áåëêîâ; ÁÎ -ãåí áåëêà îáîëî÷êè; ñãï1,2 -âåðîÿòíîå ìåñòîïîëîaeåíèå ñóáãåíîìíûõ ïðî-ìîòîðîâ 1 è 2 ñîîòâåòñòâåííî; ñãï3,Õ -ñóáãåíîìíûå ïðîìîòî-ðû 3 AltMV [14] è ÕÂÊ [11] ñîîòâåòñòâåííî; -35S ïðîìîòîð âèðóñà ìîçàèêè öâåòíîé êàïóñòû; Ä -òåðìèíàòîð ãåíà íîïà-ëèíñèíòàçû; (A)n -ïîëè(À) ïîñëåäîâàòåëüíîñòü íàçíà÷åíèÿ â òðàíñôîðìèðîâàííûõ ëèñòüÿõ Nicotiana benthamiana.  äàííîé ðàáîòå ñ öåëüþ äàëüíåéøåãî óâåëè÷å-íèÿ óðîâíÿ ïðîäóêöèè öåëåâûõ áåëêîâ â ðàñòåíèÿõ AltMV-double áûë ìîäèôèöèðîâàí.…”
Section: ðåçóëüòàòû è îáñóAeäåíèåunclassified
“…Ñõåìà ãåíîìà AltMV-MU è ñîçäàííûõ íà åãî îñíîâå âèðóñíûõ âåêòîðîâ: A -ãåíîì AltMV-MU; Á -AltMV-triple1;  -AltMV-triple2. ÒÁ 1, 2, 3 -ãåíû òðåõ òðàíñïîðòíûõ áåëêîâ; ÁÎ -ãåí áåëêà îáîëî÷êè; ñãï1,2 -âåðîÿòíîå ìåñòîïîëîaeåíèå ñóáãåíîìíûõ ïðî-ìîòîðîâ 1 è 2 ñîîòâåòñòâåííî; ñãï3,Õ -ñóáãåíîìíûå ïðîìîòî-ðû 3 AltMV [14] è ÕÂÊ [11] ñîîòâåòñòâåííî; -35S ïðîìîòîð âèðóñà ìîçàèêè öâåòíîé êàïóñòû; Ä -òåðìèíàòîð ãåíà íîïà-ëèíñèíòàçû; (A)n -ïîëè(À) ïîñëåäîâàòåëüíîñòü íàçíà÷åíèÿ â òðàíñôîðìèðîâàííûõ ëèñòüÿõ Nicotiana benthamiana.  äàííîé ðàáîòå ñ öåëüþ äàëüíåéøåãî óâåëè÷å-íèÿ óðîâíÿ ïðîäóêöèè öåëåâûõ áåëêîâ â ðàñòåíèÿõ AltMV-double áûë ìîäèôèöèðîâàí.…”
Section: ðåçóëüòàòû è îáñóAeäåíèåunclassified
“…RNA preparations enriched in low-molecular-weight RNAs from plants infected with BPMV, SMV, and both BPMV and SMV were prepared as described by Mallory et al (2003). Leaves of N. benthamiana plants were infiltrated with Agrobacterium tumefaciens harboring plasmids pGD:smGFP, expressing a soluble-modified GFP (Davis and Vierstra, 1998), alone or co-infiltrated with pGD:P19, expressing TBSV P19, pGD:HC-Pro, expressing SMV G5 HC-Pro (Lim et al, 2005), or pGD:CP, expressing SMV CP, and fluorescence was detected in epidermal cells by laser scanning confocal microscopy as described by Lim et al (2010). Low-molecular-weight RNAs from infiltrated N. benthamiana leaves and soybean plants were prepared as described (Mallory et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that replication and symptom severity of a potexvirus, Alternanthera mosaic virus, are significantly affected by a single residue change in the Triple Gene Block 1 protein viral suppressor of RNA silencing (VSR) [24]. Here we examine VSR function and subcellular localization of HC-Pro of TuMV isolates from radish, an important crop in Korea, in relation to symptom expression to determine whether the TuMV VSR has similar effects on disease severity.…”
mentioning
confidence: 96%
“…Agrobacterium transformed with pGDR:Talin (actin marker), pGD:p19 [VSR of Tomato bushy stunt virus (TBSV)], and pGD:smGFP (solublemodified green fluorescent protein) were also utilized [24,28]. Equal volumes of pGDG:HC-Pro constructs and pGDR:Talin were mixed, usually with 0.1 volume of pGD:p19; agroinfiltrated leaves [28] of N. benthamiana were examined at 2-3 days post-agroinfiltration (dpa) using a Zeiss 710 confocal microscope [29,30], with DAPI staining as described [31].…”
mentioning
confidence: 99%